Pengaruh citra merek (Brand Image) terhadap loyalitas merek produk lipstik wardah pada global kosmetik Kecamatan Tualang Kabupaten Siak - Nadia Vega; Annisa Mardatillah (Pelantar Press, 2021)
This study aims to determine the effect of brand image on brand loyalty of Wardah lipstick products in global cosmetics, Tualang District, District. In this study, for the brand, image variable uses indicators, namely attributes, benefits, overall evaluation, while for brand loyalty variables using indicators, namely measuring behavior, measuring costs, measuring satisfaction, brand liking, and commitment. The type in this study uses a descriptive type of research using quantitative methods because this study explains the relationship between the Brand Image (X) variable and the Brand Loyalty variable (Y). The sampling technique used is a purposive sampling technique or subjectively aimed sample. This research method determines respondents to be used as samples because they have specific criteria for 100 respondents. Data collection techniques are by distributing questionnaires, interviews, observations, and documentation. The data analysis technique used is simple linear analysis.